Business experience of floods and drought-related water and electricity supply disruption in three cities in sub-Saharan Africa during the 2015/2016 El Niño. (4th December 2018) - Gannon, Kate Elizabeth; Conway, Declan; Pardoe, Joanna; Ndiyoi, Mukelabai; Batisani, Nnyaladzi; Odada, Eric; Olago, Daniel; Opere, Alfred; Kgosietsile, Sinah; Nyambe, Mubita; Omukuti, Jessica; Siderius, Christian
Non-technical summary: The El Niño event in 2015/2016 was one of the strongest since at least 1950. Through surveys and interviews with key informants, we found businesses in the capital cities of Zambia, Botswana and Kenya experienced major disruption to their activities from El Niño related hydroelectric load shedding, water supply disruption and flooding, respectively. Yet, during the 2015/2016 El Niño, fluctuations in precipitation were not extreme considering the strength of the El Niño event. Results therefore highlight that even fairly moderate precipitation anomalies can contribute to major disruption to economic activity. Addressing the risk of disruption – and supporting the private sector to adapt – is a development priority. Technical summary: Drought during the 2015/2016 El Niño amplified disruption to public water supply in Botswana's capital Gaborone and contributed to unprecedented hydroelectric load shedding across Zambia. In Kenya, moderate precipitation during the El Niño brought localized floods to Nairobi and other areas. Contributing to a sparse literature on firm-level adaptation among micro, small and medium enterprise (MSMEs) in sub-Saharan Africa, through a near-real time assessment we consider MSME experience of this disruption in sectors making substantial contributions to livelihoods and national GDP. Alongside complex and indirect impact pathways that influence total loss and damage, results show varying vulnerability to disruption. Nevertheless, directly after the El Niño event, MSMEs reported water supply disruption, power outages and flooding to be the leading challenge within the business environment in Botswana, Zambia and Kenya, respectively. Deeper understanding of vulnerabilities in existing water, energy and urban infrastructure – in the context of increasing urbanization and a potentially broader range of climate variability – is urgently needed across sub-Saharan Africa. This needs to be coupled with public provision of wider enabling conditions – including access to finance – that support private sector adaptation to extreme climate events and associated resource disruption. This paper also identifies clear opportunities to improve climate information services for MSMEs.